Development of color standard for peanut butter - Pineda, Mary Margaret Nambio
Color standards were developed for a peanut butter that is most acceptable to Filipino consumers. Dry-blanched peanuts were roasted at 140°C for different periods. Consumer acceptability tests using 25 panelists were conducted to determine the most acceptable color. Samples were presented along with one imported and six local commercial peanut butters. Color analysis using instruments was rendered to know the value of L, a & b. With prolonged roasting, lightless of peanut butters attenuated from L=66.95 (raw peanuts) to L=32.62 (peanuts roasted for 60 minutes). Commercial products presented were characterized with L values that fall between 53 to 58 (53<L<58). The most acceptable color for peanut butter may be produced at 140°C for 40 minutes with L=57.65. L values between 53 to 58 were the only values highly recognized by the panel for a real or usual peanut butter. Samples with high acceptability scores were all medium brown and unstabilized peanut butter.